2009
DOI: 10.1017/cbo9780511581007
|View full text |Cite
|
Sign up to set email alerts
|

Subsystems of Second Order Arithmetic

Abstract: Almost all of the problems studied in this book are motivated by an overriding foundational question: What are the appropriate axioms for mathematics? Through a series of case studies, these axioms are examined to prove particular theorems in core mathematical areas such as algebra, analysis, and topology, focusing on the language of second-order arithmetic, the weakest language rich enough to express and develop the bulk of mathematics. In many cases, if a mathematical theorem is proved from appropriately wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
136
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(138 citation statements)
references
References 0 publications
0
136
0
2
Order By: Relevance
“…From reverse mathematics, we will concentrate on the axiom systems RCA 0 , WKL 0 , and ACA 0 , which are described in detail by Simpson [8]. Very roughly, RCA 0 is a subsystem of second order arithmetic incorporating ordered semi-ring axioms, a restricted form of induction, and comprehension for ∆ 0 1 definable sets.…”
Section: Axiom Systems and Encoding Realsmentioning
confidence: 99%
See 1 more Smart Citation
“…From reverse mathematics, we will concentrate on the axiom systems RCA 0 , WKL 0 , and ACA 0 , which are described in detail by Simpson [8]. Very roughly, RCA 0 is a subsystem of second order arithmetic incorporating ordered semi-ring axioms, a restricted form of induction, and comprehension for ∆ 0 1 definable sets.…”
Section: Axiom Systems and Encoding Realsmentioning
confidence: 99%
“…Both Simpson [8] (following Definition II.4.4) and Kohlenbach [7] (in section 4.1) encode real numbers as rapidly converging sequences of rational numbers. In particular, Simpson defines a real number as a Cauchy sequence of rationals α = α(k) k∈N satisfying ∀k∀i(|α(k) − α(k + i)| ≤ 2 −k ).…”
Section: Axiom Systems and Encoding Realsmentioning
confidence: 99%
“…Proof Working in RCA 0 , item 2 is easily deduced from Σ 0 1 -separation, which is provable in WKL 0 as shown in Lemma IV.4.4 of Simpson [8].…”
Section: Reverse Mathematicsmentioning
confidence: 97%
“…By Lemma III.1.3 of Simpson [8], we need only show that item 3 suffices to prove the existence of ranges of injections. Let f : N → N be one-to-one.…”
Section: Reverse Mathematicsmentioning
confidence: 99%
“…Extensive material related to the axiomatization and application of these subsystems to the study of complete separable metric spaces can be found in Simpson's book [5]. The codes for open sets and closed sets are sets of natural numbers, and thus elements of models of second order arithmetic.…”
mentioning
confidence: 99%